Effects of propanol isomers enrichment on in-cylinder thermochemical fuel reforming (TFR) in spark ignition natural gas engine. (1st April 2020) - Li, Bolun; Sun, Qian; Li, Ang; Shao, Yu; He, Zhuoyao; Lu, Xingcai; Huang, Zhen; Zhu, Lei
Abstract: This paper investigates the effects of propanol isomers enrichment on natural gas TFR engine via experiment and simulation. The results indicate that the reforming effect of TFR cylinder with n-propanol enrichment is the best, followed by that with iso-propanol, and with that of the natural gas being the worst. The impact of negative effect due to lack of fire was the most significant on the reforming effects with n-propanol enrichment, less on those with iso-propanol, and the least on those with natural gas. According to the kinetics analysis, the rate of H2 formation depends on the rates of H, O, OH, and HO2 formation. The n-propanol had the fastest production rate for H, O, OH, and HO2 radicals in the early stage of combustion, compared with iso-propanol and methane. The performance analysis of the normal cylinder shows that n-propanol enriched normal cylinders produced the lowest fuel consumption. Graphical abstract: Image 1 Highlights: Effects of propanol isomers on thermochemical fuel reforming were investigated. More H2 were formed during reforming process with n-propanol enrichment. The performance of TFR engine could be better with n-propanol enrichment.